‘‘Study Of Sewage Treatment Plant& Its Advancement With Innovative Approach” - Shital A. Patage, Abhay B. Shelar, Supriya B. Shinde, Krantikumar V. Mhetre (Mathematical Statistician and Engineering Applications, 2020)
A sewage treatment plant is quite necessary to receive the domestic and commercial waste and it helps to remove the materials which are harmful to general public. Its objective is to produce an environmentally safe fluid waste stream (or treated effluent) and a solid waste (or treated sludge) suitable for disposal or reuse (usually as a farm fertilizer). A study on sewage domestic waste has been performed followed by permissible limits and characteristics of various parameters of the sewage like pH, temperature, BOD, COD, TSS, TDS, acidity, alkalinity, Ammonia, Phosphorus, and also heavy metals like Copper, Zinc, Lead , Calcium, Aluminum. Also a study of different and various Journal papers has been carried out for the general conclusion of the present condition and present practices going on to treat or to minimize the sewage. A site also has been visited which gave an idea about the origin, process overview and discharge of the sewage. It also gave an idea about the capacity of the Sewage treatment plant to treat the sewage per day.